Field Survey For Chickpea Wilt In Al-Ghab, The Morphological Characteristics And Pathogenicity Of Some Isolates of Fusarium oxysporum f.sp ciceris - المغربي صباح; برهوم باسمة; علوش ليلى (Latakia University Journal -Biological Sciences Series, 2022)
A field survey for chickpea wilt disease caused by Fusarium oxysporum f.sp ciceris was conducted in 45 agricultural areas belonging to six organizational areas of Al-Ghab during 2019, which 654 samples were collected from 120 fields, The isolation resulted in 158 isolates of Fusarium oxysporum, 73 of which were selected to study their pathogenicity on the chickpea variety Ghab 3. Some isolates reduced the germination percentage of infected chickpea seeds to 50% compared to the non-infectious control 95.8%, FOC isolates showed their ability to induce disease, as high significant differences appeared between the infected treatment and the control treatment in terms of infection rate, The symptoms appeared with different degrees of yellowing, dryness of some branches, and plant wilt at high infection, and 75.34% of the isolates showed yellowing symptoms, 5.48% wilting symptoms and 19.18% of them caused yellowing and wilting symptoms together.